Sustainability Criteria for the Malaysia Homestay Programme - Maznah Mat Kasim; Kalsom Kayat; Razamin Ramli; Rohaini Ramli (International Review of Management and Marketing, 2016)
This article is based on a study that was carried out to identify all the relevant sustainability criteria for the Malaysia Homestay Programmes. The purpose of the study was to come up with the criteria which can be used by the operators to rate their services and to promote their homestays. Once the criteria are identified, they are ranked in order to discover the priority of each of the criteria. The ranking was calculated using two methods which are Modified Pairwise Comparison method and rank order centroid (ROC) method. Twelve criteria were identified as the Malaysia Homestay Programme sustainability criteria. The study established that the programmes’ ‘commitment’, ‘organizational management and ‘cooperative effect’ are found to be ranked as the three most important criteria while ‘maintenance’, ‘hospitality’, and ‘networking’ are ranked as the three least important criteria.